Peran Dosen Pembimbing Akademik Dalam Melayani Bimbingan Dan Konseling Mahasiswa Di Perguruan Tinggi - Abdulah Abdulah (Universitas Muhammadiyah Muara Bungo, 2023)
This research was conducted based on empirical findings which showed that the problem was the low level of guidance and counseling services for students to academic supervisors in universities. Therefore, it is necessary to know clearly in responding to the situation, so that the problem lies where, whether it is because of their ignorance or their lack of understanding of the existence of guidance and counseling services in universities. This study aims to determine the role of lecturers in guidance and counseling services in universities. The method used in this study is a descriptive method in the form of survey research. The research subjects are lecturers and students of the primary school teacher education study program for the 2021/2022 academic year. Based on the analysis of the data in the study, it can be concluded that the role of lecturers in guidance and counseling services is in the fairly good category.